Time-related multivariate strategy for the comprehensive evaluation of microbial chemical data - Selegato, Denise M. [UNESP]; Freitas, Thamires R.; Pivatto, Marcos; Pivatto, Amanda D.; Pilon, Alan C.; Castro-Gamboa, Ian [UNESP] (Springer Nature, 2022)
Introduction: In microbial metabolomics, the use of multivariate data analysis (MDVA) has not been comprehensively explored regarding the different techniques available and the information that each gives about the metabolome. To overcome these limitations, here we show the use of Fusarium oxysporum cultured in the presence of exogenous alkaloids as a model system to demonstrate a comprehensive strategy for metabolic profiling. Matherials and methods: F. oxysporum was harvested on different days of incubation after alkaloidal addition, and the chemical profiles were compared using LC–MS data and MDVA. We show significant innovation to evaluate the chemical production of microbes during their life cycle by utilizing the full capabilities of Partial Least Square (PLS) with microbial-specific modeling that considers incubation days, media culture availability, and growth rate in solid media. Results and Discusscion: Results showed that the treatment of the Y-data and the use of both PLS regression and discrimination (PLSr and PLS-DA) inferred complemental chemical information. PLSr revealed the metabolites that are produced/consumed during fungal growth, whereas PLS-DA focused on metabolites that are only consumed/produced at a specific period. Both regression and classificatory analysis were equally important to identify compounds that are regulated and/or selectively produced as a response to the presence of the alkaloids. Lastly, we report the annotation of analogs from the piperidine alkaloids biotransformed by F. oxysporum as a defense response to the toxic plant metabolites. These molecules do not show the antimicrobial potential of their precursors in the fungal extracts and were rapidly produced and consumed within 4 days of microbial growth.
Keywords: Biotransformation; Defense response; Fusarium oxysporum; Microbial-specific multivariate data analyses; PLS discriminant analysis; PLS regression; Toxic piperidine alkaloids